Experimental and Finite Element (FE) Studies on the Behaviour of Horizontally Curved Composite Bridges Deck - Fageer, Badria A. M.; Ahmed, A. K.; Daoud, Osama M. A. (Journal of Building and Road Research, 2021)
This paper aims to study the behaviour of horizontally curved composite steel-concrete bridges deck slab and beams under static load, using experimental tests and nonlinear finite element analysis. Two different specimens were examined in the structure laboratory, one of them was horizontally curved composite deck slab and steel girders with full interaction between the concrete deck and the steel girders, while the other with partial interaction. Each specimen has three curved I-girders acted parallel connected with X shape cross frames. Linear Variable Differential Transducers (LVDT) and strain gauges were used at critical points to measure deflections and strain respectively. Three dimensional finite element (FE) models with 137119 elements were built and analysed using ANSYS software version 14. Models dimensions were 1/10 in both length and radius of curvature of the Federal Highway Administration (FHWA) full scale model. Numerical results have been compared with the experimental test results. Maximum values and distribution of both stresses and strains at top flanges, bottom flanges and the web tension zone for numerical modelling results, showed close agreement with the experimental tests results in both full and partial interaction models. Also, similar failure modes were encountered from both numerical modelling and experimental tests. Maximum deflection values obtained from numerical modelling were slightly below the experimental values and this was attributed to the stiffer numerical model. Further, mesh refinement could have increase accuracy of numerical predictions.